Renal Angiomyolipomas in the University of Malaya Medical Centre: Its Spectrum of Presentation and Management - Koh, P.S.; Muhilan, P.; Dublin, N.; Razack, A.H. (Faculty of Medicine, University of Malaya, 2009)
Renal angiomyolipoma, once considered a rare benign renal tumour, is relatively common these days. They account for 0.3-3.0% of all renal masses. Histologically, it is composed of adipose tissue, smooth muscles and blood vessels. Here, we wish to highlight five cases of renal angiomyolipomas which were presented to the University Malaya Medical Centre (UMMC), Kuala Lumpur, Malaysia, over a two-year period between June 2005 and June 2007. This study wish to illustrate its varied clinical presentation and the management undertaken for each underlying condition. These cases were presented in the form of spontaneous perirenal haemorrhage, a large asymptomatic renal mass, a small asymptomatic renal mass, a symptomatic renal angiomyolipoma and a case of renal angiomyolipoma mimicking a renal tumour. Each of these cases varied in its clinical presentation; thus, management has become very challenging to clinicians ranging from conservative management to active intervention, be it operatively or non-operatively.